2012
DOI: 10.1111/j.1468-5922.2012.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Monuments of memory: defensive mechanisms of the collective psyche and their manifestation in the memorialization process

Abstract: The paper searches for insight in the area of collective memory as a part of collective consciousness, a phenomenon understood as a stabilizing factor for a society's self-image and identity. Collective memories are seen as originating from shared communications transmitting and creating the meaning of the past in the form of narrative, symbols and signs. As such, they contain the individual, embodied and lived side of our relations to the past. As well as the identity-building and meaning-making functions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In this way the non‐commemoration of the dissonant heritage of Spassk 99, Mamochkino, and Osakarovka can be explained if not understood. Kalinowska () referred to this as defensive elements in the collective psyche providing a stabilizing context for national identity. Research in this area frequently relates to the holocaust and the collective trauma of genocide (Mazur & Vollhardt, ).…”
Section: Methodsmentioning
confidence: 99%
“…In this way the non‐commemoration of the dissonant heritage of Spassk 99, Mamochkino, and Osakarovka can be explained if not understood. Kalinowska () referred to this as defensive elements in the collective psyche providing a stabilizing context for national identity. Research in this area frequently relates to the holocaust and the collective trauma of genocide (Mazur & Vollhardt, ).…”
Section: Methodsmentioning
confidence: 99%
“…In relation to other European countries, Kalinowska (2012) has addressed cultural issues from within the Polish context, commenting that ‘collective consciousness and its defences are shaped by traumatic memories of the past’ (p. 440) so that trauma could remain unmourned. From their experience of training in Poland, Mathers et al (2006) not only spoke of post‐Communist cultural trauma but noticeably the use that could be made of certain archetypal patterns, when they emerged.…”
Section: European Router Experiencesmentioning
confidence: 99%
“…Collective memory suggests collaboration of a group or community, regarding the way in which an event is remembered or memorialised and how it continues to have a bearing on that community 15 . It is perhaps one of the most important aspects of a mass trauma event as it provides a shared medium through which individuals can remember the events or articulate themselves through the shared stories 16 . It has been suggested that where there has been collective trauma the sharing of collective memories is essential to the healing process 17 .…”
Section: Remembering Life Eventsmentioning
confidence: 99%